Thermal and Optical Characterization of Polymer-Dispersed Liquid Crystals - Robert A. Shanks; Daniel Staszczyk (International Journal of Polymer Science)
Liquid crystals are compounds that display order in the liquid state above the melting temperature and below the mesogenic isotropic temperature. Polymer-dispersed liquid crystals (PDLCs) are composite materials in which liquid crystalline material is dispersed within a polymer matrix to form micron-sized droplets. The aim was to prepare several cholesteryl esters or alkoxybenzoic acid PDLCs and characterise thermal and optical properties. Differential scanning calorimetry and polarized optical microscopy were employed. The matrix polymer was a one-component UV-curable epoxy-acrylate resin. PDLCs were formed through entropy controlled phase separation resulting from UV-initiated crosslinking. The liquid crystals, both as mesogenic moieties and as dispersed droplets, exhibited various textures according to their molecular order and orientation. These textures formed in constrained regions separated by phase boundaries that occurred at temperatures characteristic of each liquid crystal used. The PDLC phase transitions occurred at temperatures lower than those exhibited by the mesogenic components in the neat state.